Ranaviruses Emerging Pathogens of Ectothermic Vertebrates - Gray, Matthew J.; Chinchar, V. Gregory; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This is a open access book. Ranaviruses, double-stranded DNA viruses (family Iridoviridae) that cause systemic, life-threatening disease in a variety of amphibians, reptiles and fish, have contributed to mass die-offs of both wild and captive populations around the globe. These viruses are emerging and increasingly responsible for population declines of ectothermic vertebrates. Because amphibians, reptiles, and freshwater turtles are suitable hosts and among the most imperiled vertebrate taxa in the world, ranaviruses can have significant impacts on biodiversity and ecosystem function. Additionally, many fish that are raised in aquaculture facilities and traded internationally are suitable hosts; thus, the potential economic impact of ranaviruses is significant. Ranaviruses also serve as a model for understanding viral replication and gene function among large double-stranded DNA viruses, e.g., poxviruses, asfarvirus, and ascoviruses. Lastly, study of the host immune response to ranaviral disease and the identification of viral immune evasion genes that negatively regulate host immune functions provide insight into which specific immune elements are most important in protecting host species against severe disease. The effort to produce a 2nd edition of our earlier work grew out of a recent meeting (1st Global Amphibian and Reptile Disease Conference) held in August 2022. Given the continued research in ranaviruses and ranaviral disease since the first edition, this new book updates the latest information on ranaviruses and provides guidance on how to monitor and manage ranaviruses in cold-blooded vertebrate populations.
Chapter 1 Introduction: Ranaviruses Past, Present and Future -- Chapter 2 Ranavirus taxonomy and phylogeny -- Chapter 3 Ranavirus replication: New studies provide answers to old questions -- Chapter 4 Immune defenses against ranavirus infections -- Chapter 5 Characterization, pathogenesis and immune-biological control of Singapore grouper iridovirus (SGIV) -- Chapter 6 Ranavirus distribution and host range -- Chapter 7 Ranavirus ecology: From individual infections to population epidemiology to community impacts -- Chapter 8 Pathology and diagnostics -- Chapter 9 Design and analysis of ranavirus studies: Insights into planning surveillance, modeling host-pathogen dynamics, and performing risk analyses.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Vertebrates; Virology; Biotic communities; Applied ecology; Microbial ecology; Vertebrate Zoology; Virology; Ecosystems; Applied Ecology; Microbial Ecology